Current Utilization and Research Status of Traditional East Asian Herbal Medicine Treatment for Multiple Sclerosis: A Scoping Review - Seo, Yuna; Jin, Chul; Cho, Seung-Yeon; Park, Seong-Uk; Jung, Woo-Sang; Moon, Sang-Kwan; Park, Jung-Mi; Ko, Chang-Nam; Cho, Ki-Ho; Kwon, Seungwon (Frontiers in Neurology, 2021)
Background: Multiple sclerosis (MS) is a chronic immune-mediated inflammatory disease of the central nervous system that is gradually increasing in prevalence. The etiology of MS remains unknown; however, it is assumed to be caused by a deterioration of autoimmune regulation. Although immunomodulatory agents are a standard treatment option in patients with MS, there is insufficient evidence about their clinical efficacy in symptomatic treatment, and many MS patients resort to complementary and alternative medicine. For this reason, we conducted a scoping review to investigate the current status of the clinical evidence related to traditional East Asian herbal medicine treatment for MS and to inform future research and treatment strategies. Method: A scoping review is an emerging methodology for knowledge synthesis that adopts the Arksey and O’Malley framework. The research question was, “What has been studied about the herbal medicine treatments administered to patients with MS?” Articles published until 2019 were identified in six databases (PubMed, Embase, Cochrane, KoreaMed, NDSL, and OASIS) in March of 2020. Data from the included studies were charted and descriptively analyzed in relation to the study’s research questions. Results: Of the 1,445 articles identified, 14 studies were included in this review. Single and serial case reports constituted the majority (42.86%), with 57.14% of studies conducted in China. A total of 20 prescriptions containing 95 herbs were used in the intervention and observational studies. Herbal medicines were effective at improving clinical symptoms of MS and reducing recurrence frequency. The main cause of MS was presumed to be oxidative stress, which enhances inflammation and, consequently, causes neuronal death. Conclusion: Herbal medicines were determined to improve the symptoms of MS and to reduce the frequency of recurrences. This study suggests that herbal medicines are promising and worth pursuing further studies but the state of current evidence is poor. Thus further, high-quality studies included larger randomized trial are required.